Comparing the effectiveness of extracorporeal shockwave therapy and myofascial release therapy in chronic pelvic pain syndrome: study protocol for a randomized controlled trial - Ningqing Huang; Zhi Qin; Wudong Sun; Kaiming Bao; Jingxian Zha; Peng Zhang; Panpan Feng; Xiaojun Zhao; Mengqian Liu; Jinjun Shi; Ming Ma (Trials, 2023)
Abstract Background Chronic prostatitis/chronic pelvic pain syndrome is a highly prevalent syndrome. Previous studies showed that extracorporeal shockwave therapy and myofascial release therapy could improve the quality of life in patients with chronic prostatitis/chronic pelvic pain syndrome (CP/CPPS). Theoretically, combined therapy with extracorporeal shockwave therapy and myofascial release therapy will likely have significant advantages in treating CP/CPPS. We, therefore, present a protocol for conducting a well-designed randomized controlled trial to compare the efficacy and safety of each therapy. Methods The proposed study will be a three-group randomized control trial (RCT) design that includes 150 participants from Zhongda Hospital Affiliated to Southeast University, with equal allocation of participants to the three intervention groups. The study duration will be 8 weeks, which includes a 4-week treatment period and a 4-week follow-up period. The primary outcome will be the changes in surface electromyography (sEMG) assessment and National Institutes of Health-Chronic Prostatitis Symptom Index (NIH-CPSI). The secondary outcomes will include the changes in three-dimensional quantification, shear wave elastography (SWE), and sympathetic skin response (SSR) testing. Assessments will be conducted before the intervention (T0), before the 5th intervention (T1), immediately after the 8th intervention (T2), and the 4th week after the end of the 8th intervention (T3). Discussion This trial will compare the differences in efficacy between single extracorporeal shockwave therapy, single myofascial release therapy, and combined therapy to select the most appropriate treatment option for patients with CP/CPPS. The possible pathogenesis of CP/CPPS would also be analyzed by comparing the intercorrelation between each objective and subjective measurement (NIH-CPSI score, sEMG, SWE, SSR). Trial registration The name of the registry: Extracorporeal Shockwave and Myofascial Release Therapy in Chronic Pelvic Pain Syndrome. Registration number: NCT05659199. Date of registration: December 2022.